1990
DOI: 10.3109/02713689009069933
|View full text |Cite
|
Sign up to set email alerts
|

Arterial pulse modulates steady-state ocular accommodation

Abstract: Rapid and continuous fluctuations in ocular focus are known to occur when the eye views a stationary target. The advent of high-speed infra-red optometers has established that these microfluctuations of ocular accommodation have two dominant components: low frequency of less than 0.6 Hz and high frequency between 1.0-2.3Hz. Although the retinal image blur associated with microfluctuations has the potential to guide and maintain optimum accommodation levels, there is no consensus with regard to the respective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 18 publications
8
59
0
Order By: Relevance
“…[17][18][19] In our investigation of the correlation between the microfluctuations in ocular surface wavefront aberrations and pulse and instantaneous heart rates, we found that they were not correlated. We believe that the microfluctuations in the ocular surface wavefront aberrations are primarily the results of the dynamics of the tear film and blinking 20 rather than pulse and instantaneous heart rate.…”
Section: Figurementioning
confidence: 71%
“…[17][18][19] In our investigation of the correlation between the microfluctuations in ocular surface wavefront aberrations and pulse and instantaneous heart rates, we found that they were not correlated. We believe that the microfluctuations in the ocular surface wavefront aberrations are primarily the results of the dynamics of the tear film and blinking 20 rather than pulse and instantaneous heart rate.…”
Section: Figurementioning
confidence: 71%
“…Thus, there is no overlap of responses by the fast and slow components, which would have caused conflicting commands and potential response instability. It should be pointed out that the previously observed 2 Hz accommodative oscillations under steady viewing conditions (Campbell et al, 1959;Charman and Heron, 1988) has been shown to be an artefact of the arterial pulse on the accommodation measurement device (Winn et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Eye movements and instrument noise contribute only marginally to the measured fluctuations [14]. To date, only the effects of pulse and respiration have been clearly identified in the accommodative signal via coherence analysis [2], [7], [8]. These effects have not been confirmed in the wavefront aberration signal, where the frequency component that could be related to a pulse signal was only occasionally observed [14].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, two main spectral regions are identified for the accommodative fluctuations: the lower frequency region, Hz, and the higher frequency region, Hz. Simple Fourier-transform-based techniques and the coherence analysis have been used to link changes in the accommodation fluctuations with pulse and respiration signals [2], [7], [8].…”
Section: Introductionmentioning
confidence: 99%